Modeling a new computer framework for managing healthcare organizations : balancing and optimizing patient satisfaction, owner satisfaction, and medical resources - Oueida, Soraia (New York, NY : Routledge, 2021)
"The medical sector has been growing largely over the last decade and healthcare services are becoming more complex and costly. In order to continue efficiently and effectively managing patient safety, quality and the effectiveness of the healthcare systems, new methodologies are needed. This book provides a platform to address this growing need and improve practice. With the introduction of a new computer platform package for the management of medical organizations and healthcare systems, this book aims to improve management techniques and increase overall satisfaction scores of patients, owner and medical resources. The platform outlined will improve the daily operation of a healthcare system, focusing on the emergency department, and can be used to study the operation flow of a unit for performance optimization. It offers a user-friendly interface and proposed programing language, along with a visual and simply way to collect and understand statistical outputs. Essential reading for decision makers on different levels in the healthcare organization hierarchy, this book can also be used by management to improve the performance of the organization, and targets decision makers to hire resources, enhance workflows or both. It guides designers and system implementers in a step-by-step approach to make optimal decisions for resource allocation and it helps designers and management to detect deficiencies in the ongoing process and fix or enhance them"--
"A Productivity Press book."
OCLC-licensed vendor bibliographic record.
Keywords: Health services administration; Health services administration -- Management; Health services administration -- Technological innovations